2011
DOI: 10.1002/kin.20624
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on N‐Mannich bases of 3‐hydrazonoindolin‐2‐one in water–ethanol and water–acetonitrile mixtures

Abstract: Various isatin-N-Mannich bases have shown antiviral and tuberculosatic activity. A reaction of 3-hydrazonoindolin-2-one was performed efficiently with morpholine in the presence of formaldehyde. Kinetic studies have revealed no reaction between 3-hydrazonoindolin-2-one and morpholine in the absence of formaldehyde. The reaction was found to obey the pseudo-first-order kinetics. It was carried out at the temperature range of 30-60 • C and at different percentage compositions of aqueous ethanol and aqueous aceto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Effect of base: Comparing the data obtained in this study Table-1 and previous one 16 showed that the rate in our study is greater as twice than the previous one where the base used is morpholine.…”
Section: Kinetic Measurmentsupporting
confidence: 51%
See 1 more Smart Citation
“…Effect of base: Comparing the data obtained in this study Table-1 and previous one 16 showed that the rate in our study is greater as twice than the previous one where the base used is morpholine.…”
Section: Kinetic Measurmentsupporting
confidence: 51%
“…Schiff and Mannish bases of isatin derivatives were reported to show variety of biological activities like antibacterial 4 , antifungal 5 , anticonvulsant 6 , anti HIV 7 , antidepressant 8 and antiinflammatory 9 activities. Because of the importance of the subject and as our continuation studies in the field of solvent effect on reaction rate [10][11][12][13][14][15][16][17][18] , it was, therefore, as a matter of interest to submit this reaction to kinetic studies. The kinetics were measured in mixed solvent media of water with ethanol and water with acetonitrile (up to 70 %), where, pH of the medium was ca.…”
Section: Introductionmentioning
confidence: 99%
“…Ethanol molecules represent very short amphiphiles that interact with each other and with water molecules in a defined nonideal manner dependent on the ratio of the two solvents 24. Furthermore, ethanol molecules establish hydrogen bonds and hydrophobic interactions with solutes present in the mixture, enabling control on different chemical reactions, including hydrolysis of different molecules 25–28. Specifically, ethanol–water solvent mixtures were found29 to selectively lower the rate of acidic hydrolysis of alkyl substituted amides, which becomes more pronounced with increasing the alkyl chain length from methyl to ethyl and propyl.…”
Section: Introductionmentioning
confidence: 99%